Electrochemical characterization of individual oil micro-droplets by high-frequency nanocapacitor array imaging. (14th December 2021) - Renault, Christophe; Laborde, Cecilia; Cossettini, Andrea; Selmi, Luca; Widdershoven, Frans; Lemay, Serge G.
Abstract : CMOS-based nanocapacitor arrays allow local probing of the impedance of an electrolyte in real time and with sub-micron spatial resolution. We report on the physico-chemical characterization of individual microdroplets of oil in a continuous water phase. Abstract : CMOS-based nanocapacitor arrays allow local probing of the impedance of an electrolyte in real time and with sub-micron spatial resolution. Here we report on the physico-chemical characterization of individual microdroplets of oil in a continuous water phase using this new tool. We monitor the sedimentation and wetting dynamics of individual droplets, estimate their volume and infer their composition based on their dielectric constant. From measurements before and after wetting of the surface, we also attempt to estimate the contact angle of individual micron-sized droplets. These measurements illustrate the capabilities and versatility of nanocapacitor array technology.